Self-Disclosure in Interpersonal Communication among Students with Autism Spectrum Disorder (ASD) in One-on-One Learning - Ricelin Novinda Mutiara Ramadhani; Sumardjijati (Lavish Opulent Education, 2026)
Communication characteristics of students with Autism Spectrum Disorder influence the process of self disclosure in interpersonal communication. This study aims to analyze the role of the one-on-one class learning system at SLB Harapan Bunda Surabaya in supporting students’ self-disclosure based on the dimensions of self-disclosure proposed by Joseph A. DeVito. This research employed a descriptive qualitative method with data collection techniques including in depth interviews, observation, and literature study. The study found that the one-on-one learning approach creates intensive and supportive interpersonal relationships that help students gradually develop self-disclosure. The process is influenced by emotional conditions, feelings of comfort, and closeness with teacher assistants, and is expressed through both verbal and nonverbal communication. The dimensions of valence, as well as purpose and intention, were found to be more relevant in the self-disclosure process of ASD students, while the dimensions of amount, accuracy, and depth have not developed optimally due to students’ communication limitations.